Resonant Damping and Instability of Propagating Magnetohydrodynamic Body Modes in a Flux Tube with Shear Flow under Photospheric Conditions - D. J. Yu (The Astrophysical Journal)
The influence of shear flow on resonant absorption is theoretically investigated for propagating magnetohydrodynamic body modes in cusp (slow) and Alfvén continua in a cylindrical flux tube under photospheric conditions. An analytical dispersion relation for resonant absorption in the presence of flow shear is developed by assuming a thin boundary layer. The numerical solutions reveal that the presence of flow shear has a rather negative impact on the resonant absorption of the body mode compared to the surface modes. As the flow shear increases, it first slightly increases the strength of resonant absorption for the forward body modes and then decreases it below the strength of no flow shear case for both resonances. It is also found that as the flow shear increases, the range of the axial wavenumber and wave frequency for the cusp resonance decreases when the wave frequency is close to the upper boundary of the cusp continuum. For the backward body modes, the strength of the resonance absorption decreases with the increment of the flow shear. When the flow shear is sufficiently large, the waves propagate in the forward direction, and their amplitude grows with a small increment.